One-Shot Dilation in Modified Supine Position for Percutaneous Nephrolithotomy: Experience From Over 300 Cases - Harrech, Youness El; Abakka, Najib; Anzaoui, Jihad El; Goundale, Omar; Touiti, Driss (Urology Journal, 2014)
<!–[if gte mso 9]> <![endif]–> <!–[if gte mso 9]> Normal 0 false false false EN-GB JA X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:Cambria; –> <!–[endif] –> <!–StartFragment–> Abstract Purpose: To evaluate the feasibility, safety and efficacy of one-shot dilation (OSD) in modified supine position percutaneous nephrolithotomy (PCNL). Materials and Methods: A total of 320 PCNL in a total of 291 patients were performed between October 2008 and July 2011. There were no specific exclusion criteria. Patients with kidney anomalies or solitary kidney, with history of renal surgery or extracorporeal shockwave lithotripsy (SWL), those with staghorn calculi or needing more than one access, were eligible for inclusion. Data collected included patient demographics and stone characteristics, access time, radiation exposure, total operating time, preoperative and postoperative hemoglobin concentrations, tract dilatation failures, complications and transfusions. Results: Mean stone size was 38 mm (16-110 mm). The mean time access was 2.1 min (range 0.7-6.2 min). Tract dilatation fluoroscopy time was 25 ± 17 sec. The targeted calix could be entered with a success rate of 97.81%. The mean hemoglobin decrease was –1.17 g/dL ± 0.84. There were no visceral, pleural, collecting systems or vascular injuries. Major complications included, transfusion in 4 (1.25%) patients, pseudoaneurysm with persistent bleeding necessitating nephrectomy in 1 (0.3%) patient and two deaths (0.62%) after surgery. There was no significant difference in successful access and complications between patients with and without previous open surgery and in those with or without staghorn stones (P > .05). Conclusion: The use of one shot and modified supine position combines the advantages of these both methods including less radiation exposure and shorter access and operative time. The one shot dilation is safe, easy to learn, cost effective and offers a potential alternative to the standard devices particularly in developing countries. <!–EndFragment–>